Digital Inequity in Health Access: A Literature Review of Ayushman Bharatand ABDM in India (Indian Journal of Public Health Research & Development, 2026)
Background:Ayushman Bharat, launched in 2018, is India’s flagship initiative toward Universal Health Coverage through the Pradhan Mantri Jan Arogya Yojana (PM-JAY) and strengthened primary healthcare services. The Ayushman Bharat Digital Mission (ABDM), introduced in 2021, further aims to improve healthcare access, efficiency, and transparency through digital health innovations. However, emerging evidence suggests that digital inequities may limit equitable access to these initiatives, particularly among rural, low-income, and digitally marginalised populations.Objective:This review examines the role of digital barriers in shaping access to and utilisation of Ayushman Bharat and ABDM, with a focus on digital literacy, infrastructure, awareness, trust, and ethical concerns within the Indian healthcare context.Methods:A narrative literature review was conducted using PubMed, Google Scholar, government reports, and policy documents published between 2018 and 2025. Relevant studies were identified using key search terms related to Ayushman Bharat, ABDM, digital health, and healthcare access in India, and were thematically synthesised.Results:The review identified persistent gaps in awareness and utilisation of PM-JAY and ABDM, especially in rural and underserved areas. Major barriers included low digital literacy, inadequate internet connectivity, limited access to digital devices, and concerns regarding data privacy and system trust. While digital tools such as ABHA IDs, electronic health records, and telemedicine platforms offer significant potential, their benefits remain unevenly distributed. Community-based intermediaries, including ASHAs and Ayushman Mitras, play a crucial role in bridging digital gaps, though systemic challenges persist.Conclusion:Despite notable progress, digital inequities continue to constrain the equity goals of Ayushman Bharat and ABDM. Strengthening digital literacy, ensuring data protection, expanding infrastructure, and maintaining offline access mechanisms are essential for achieving inclusive and equitable Universal Health Coverage in India.
Keywords: Digital inequity; Ayushman Bharat